Vapor-Assisted Method to Deposit Compact (CH3NH3)3Bi2I9 Thin Films for Bismuth-Based Planar Perovskite Solar Cells - Zihao Gao; Xinjie Wang; Zhen Sun; Ping Song; Xiyuan Feng; Zhixin Jin (Micromachines)
Bismuth-based perovskite derivatives, (CH3NH3)3Bi2I9 (MBI), are promising non-toxic light-absorbing materials widely used in various photoelectric devices because of their excellent stability. However, MBI-based perovskite solar cells (PSCs) are limited by poor film quality, and the performance of such a device is far behind that of lead-based PSCs. In this work, the crystal structure and morphological properties of MBI films were compared across different preparation methods. The two-step vapor-assisted method can prepare continuous dense MBI films because MBI crystal nucleation is induced by the BiI3 seed layer. The MBI film grown by this method is better for the production of excellent PSCs compared to the film prepared by the solution method. The best photovoltaic device based on the MBI film could obtain a power conversion efficiency of 1.13%. An MBI device is stored in the glove box for 60 days, and the device’s performance is maintained at 99%. These results indicate that the vapor-assisted deposition of MBI films can be an effective method to improve the performance of bismuth-based planar PSCs.